How Can We Get to Equitable and Effective Postpartum Pain Control?. Issue 3 (13th September 2022) - Johnson, Jasmine D.; Cooper, Shontreal; Badreldin, Nevert; Green, Celeste
Abstract : Postpartum pain is common, yet patient experiences and clinical management varies greatly. In the United States, pain-related expectations and principles of adequate pain management have been framed within established norms of Western clinical medicine and a biomedical understanding of disease processes. Unfortunately, this positioning of postpartum pain and the corresponding coping strategies and pain treatments is situated within cultural biases and systemic racism. This paper summarizes the history and existing literature that examines racial inequities in pain management to propose guiding themes and suggestions for innovation. This work is critical for advancing ethical practice and establishing more effective care for all patients.